2015
DOI: 10.3389/fneur.2015.00263
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Percent Prevalence of Extracampine Hallucinations in Parkinson’s Disease Patients

Abstract: Extracampine hallucinations (EH), the sense of a presence or fleeting movement in the absence of an associated visual percept, have been reported in Parkinson’s disease (PD) patients but their prevalence, characteristics, and temporal relationship to visual hallucinations (VH) remain unclear. Given that, VH are predictive of cognitive impairment in PD, improved understanding of EH may have significant prognostic implications. The objective of this study is to evaluate the prevalence and characteristics of EH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…The authors showed that the sense of presence is a significant independent predictor of VHs (odds ratio [OR] 4.5). Similarly, Wood et al 15 revealed that patients with MHs are significantly more likely to have concomitant VHs. However, the relationship between MHs and cognitive impairment has not been demonstrated in PD patients, although formed VHs are generally considered to be linked to cognitive impairment according to a number of studies 7,8,16 .…”
Section: Introductionmentioning
confidence: 91%
“…The authors showed that the sense of presence is a significant independent predictor of VHs (odds ratio [OR] 4.5). Similarly, Wood et al 15 revealed that patients with MHs are significantly more likely to have concomitant VHs. However, the relationship between MHs and cognitive impairment has not been demonstrated in PD patients, although formed VHs are generally considered to be linked to cognitive impairment according to a number of studies 7,8,16 .…”
Section: Introductionmentioning
confidence: 91%
“…An online questionnaire administered to individuals with PD suggested an overall prevalence of 50% for presence and passage hallucinations (‘extracampine hallucinations’ was used as a collective term for both experiences, although this differs from its classic usage), with individual prevalences of 25% for presence hallucinations and 46% for passage hallucinations 12 . Studies of formed hallucinations in PD have found an association between the cognitive profile and the type of hallucination experienced 13 : patients with PD whose typical hallucinations are of unfamiliar content (for example, unidentified figures) have more-profound deficits of inhibitory executive function than do patients with hallucinations that are recognized (for example, family members).…”
Section: Phenomenology and Diagnosismentioning
confidence: 99%
“…Passage (feeling like something is passing at the outer visual field) and presence (feeling that someone is close by) hallucinations as well as illusions (mis-or distorted perception of an actual stimulus) are the most common symptoms at early stage of the disease. Passage and presence hallucinations may concern 50% of the patients (Wood et al, 2015). As the disease progresses, visual hallucinations in PD may be complex and formed, usually vision of animals, people or objects.…”
Section: Psychosismentioning
confidence: 99%